Training to Improve Achievement at Aceh-Sumut Pon 2024 the International Boxing Association Standard Referee - khaerul Khaerul Anam; Muhammad Riyan Hidayatullah; Aji Nurrizqi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this service is to increase the human resources for amateur boxing at the provincial level by uniting in achieving achievements at the 2024 Aceh-North Sumatra PON, several agreements from partners include providing national standard training and refreshments for those who are certified. The solution to the problem was agreed only to provide training/upgrading of regional referees. The results of the activity went well. In the initial pre-test data, 65% answered correctly out of 10 questions given by the committee and 85% of the post-test results were almost perfect out of 10 questions. The conclusion to go to international standard training requires a lot of money, it is necessary to have a derivative from each participant who has passed the basic qualifications. suggestions in the following service to refresh the quality of referees must continue to be carried out in stages as a scientific reflection.